Diagnosis and treatment outcomes of adult tuberculosis in an urban setting with high HIV prevalence in Sierra Leone: A retrospective study. (July 2020) - Lakoh, Sulaiman; Jiba, Darlinda F.; Adekanmbi, Olukemi; Poveda, Eva; Sahr, Foday; Deen, Gibrilla F.; Foray, Lynda M.; Gashau, Wadzani; Hoffmann, Christopher J.; Salata, Robert A.; Yendewa, George A.
Highlights: Sierra Leone is a high tuberculosis (TB) burden country, yet studies on the TB epidemic in this country are lacking. Poor treatment outcomes were observed, characterized by high TB/HIV prevalence at the national referral treatment center in 2017. HIV-positive status and age 65 years or older independently predicted death. More action is warranted to improve TB care as the country intensifies efforts to achieve the 2035 global TB elimination goals. Abstract: Objective: To assess the diagnosis, treatment outcomes, and predictors of mortality in adult tuberculosis (TB) patients in an urban setting with a high HIV prevalence. Methods: A retrospective study was conducted of adult TB patients aged ≥15 years who were treated at Connaught Hospital in Freetown, Sierra Leone from January through December 2017. Multivariate logistic regression was used to identify predictors of mortality. Results: Of 1127 TB cases notified in 2017, 1105 (98%) were tested for HIV, yielding a TB/HIV co-infection rate of 32.0%. Only HIV-tested cases ( n =  1105) were included in the final analysis. The majority were male (69.3%), aged 25–34 years (29.2%), and had pulmonary TB (96.3%). Treatment outcomes were as follows: 29.0% cured, 29.0% completed, 0.5% treatment failure, 24.2% lost to follow-up, 12.8% transferred/not evaluated, and 4.5% died. The majority of deaths (80.0%, 40/50) occurred within 2 months of TB treatment initiation. Age 65 years or older (adjusted odds ratio 3.48, 95% confidence interval 1.15–10.56; p =  0.027) and HIV-positive status (adjusted odds ratio 3.50, 95% confidence interval 1.72–7.12; p =  0.001) were independent predictors of mortality. Conclusions: Suboptimal TB treatment outcomes were observed in Sierra Leone in 2017. More local and international action is warranted to help achieve the 2035 global TB elimination targets.